Gastroparesis Symptoms Associated with Intestinal Hypomotility: An Explorative Study Using Wireless Motility Capsule - Bekkelund M (Clinical and Experimental Gastroenterology, 2021)
Mattis Bekkelund,1,2 Dag A Sangnes,2– 4 Eirik Søfteland,3– 5 Lars Aabakken,1,6 Martin Biermann,4,7 Elisabeth K Steinsvik,2,4,8 Trygve Hausken,2,8 Georg Dimcevski,4,8 Jan Gunnar Hatlebakk2– 4 1Department of Clinical Medicine, University of Oslo, Oslo, Norway; 2Norwegian Competence Centre for Functional Gastrointestinal Disorders, Department of Medicine, Haukeland University Hospital, Bergen, Norway; 3Department of Medicine, Haukeland University Hospital, Bergen, Norway; 4Department of Clinical Medicine, University of Bergen, Bergen, Norway; 5Hormone Laboratory, Haukeland University Hospital, Bergen, Norway; 6Department of Transplantation Medicine, Section for Gastroenterology, Oslo University Hospital, Oslo, Norway; 7Centre for Nuclear Medicine and PET, Department of Radiology, Haukeland University Hospital, Bergen, Norway; 8National Centre for Ultrasound in Gastroenterology, Haukeland University Hospital, Bergen, NorwayCorrespondence: Mattis BekkelundNorwegian Competence Centre for Functional Gastrointestinal Disorders, Department of Medicine, Haukeland University Hospital, Bergen, 5021, NorwayTel +47 48 18 68 97Email mattis.bekkelund@hotmail.comObjective: Gastric emptying measurements are mandatory in gastroparesis diagnostics, but the association between delayed emptying and symptoms is questionable. It is imperative to find biomarkers better correlated to symptom generation. Hence, we examined the association between symptom severity and gastrointestinal motility measured by wireless motility capsule.Patients and Methods: In this prospective single-centre study, patients with gastroparesis symptoms were simultaneously investigated with gastric emptying scintigraphy and wireless motility capsule, measuring regional transit times and contractility parameters. Symptom severity was assessed with the Patient Assessment of Upper Gastrointestinal Symptom Severity Index (PAGI-SYM), including the Gastroparesis Cardinal Symptom Index (GCSI).Results: We included 107 patients (70% women). In the whole patient group, nausea correlated with the gastric (rs = − 0.31, p = 0.007), small bowel (rs = − 0.41, p < 0.001) and colonic (rs = − 0.33, p = 0.012) motility indices. In patients with idiopathic etiology, nausea correlated with small bowel motility index (rs = − 0.81, p < 0.001) and mean stomach pressure (rs = − 0.64, p = 0.013). We also found negative correlations between total GCSI score and maximum pressure of the small bowel (rs = − 0.77, p < 0.001) and colon (rs = − 0.74, p = 0.002). In diabetes patients, total PAGI-SYM score correlated with colonic motility index (rs = − 0.34, p = 0.012), and mean pressure of the colon correlated with upper abdominal pain (rs = − 0.37, p = 0.007). We found no association between symptoms, gastric emptying nor any other transit times.Conclusion: In patients with gastroparesis symptoms, we found that symptom severity was associated with intestinal hypomotility. Based on these results, gastroparesis diagnostics should also include an evaluation of the small bowel and colon.Keywords: gastric emptying, gastrointestinal motility, gastroparesis, gastroparesis-like syndrome, small bowel, wireless motility capsule, scintigraphy